Synthesis of cyanoethyl- and carbamoylethylcellulose - Roulamo, Anneli (2003)
The tentative plan of the research described in this study was to clarify a possibility to use cyanoethylation of cellulose as an intermediate step in the synthesis of carboxyethylcellulose. During the work it turned out that compared to cyanoethylation carbamoylethylation of cellulose provides a better intermediate for the conversation for the final product. Especially, the effect of common organic solvents on the degree of substitution was studied. Guidelines for synthesis of water-soluble carbamoylethyl-carboxyethyl cellulose mixed ether in xylene are described. Characterisation of the products was carried out by means of NMR spectroscopy, FTIR spectroscipy, and the analysis of nitrogen (Kjeldahl) and sodium carboxylate content.